2011
DOI: 10.1007/s00261-011-9756-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of tumor vascularity and its relationship to cytokeratin 19 expression in patients with hepatocellular carcinoma

Abstract: Hypovascular HCCs were associated with early recurrence and short overall survival, and CK19 was more frequently expressed in hypovascular HCC than in hypervascular tumors. Therefore, tumor vascularity on CT images might be utilized in determining the prognosis of patients with HCCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Studies investigating tumor vascularity as a factor impacting treatment outcome after TACE showed that high serum VEGF levels were significantly correlated with poor outcomes after TACE [ 30 ]. However, other studies showed that patients with hypovascular HCC had a poorer response, poorer survival, and early recurrence compared to patients with hypervascular tumors [ 3 , 18 , 20 , 21 ], possibly because the chemotherapeutic agent or embolic agent is more efficiently delivered to tumors with a good arterial supply. These data suggested that the role of tumor vascularity in treatment response and OS is not completely understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies investigating tumor vascularity as a factor impacting treatment outcome after TACE showed that high serum VEGF levels were significantly correlated with poor outcomes after TACE [ 30 ]. However, other studies showed that patients with hypovascular HCC had a poorer response, poorer survival, and early recurrence compared to patients with hypervascular tumors [ 3 , 18 , 20 , 21 ], possibly because the chemotherapeutic agent or embolic agent is more efficiently delivered to tumors with a good arterial supply. These data suggested that the role of tumor vascularity in treatment response and OS is not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, TACE was found to be as effective as hepatic resection when lipiodol was compactly retained within the tumor [ 17 ]. Additionally, patients with well-differentiated, hypovascular HCC tumors responded poorly to TACE, had a shorter OS, and were associated with early recurrence compared to patients with well-differentiated hypervascular tumors [ 18 , 19 , 20 , 21 ]. However, in patients with unresectable HCC treated with TACE, OS was higher in hypervascular responders, and in hypervascular non-responders and hypovascular responders compared to hypovascular non-responders [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in subjects with HCC, k19 expression showed a correlation not only with morphological tumor parameters (increased tumor size, poor grade differentiation, microvascular invasion) in both surgical specimens and in samples obtained by fine needle biopsy [100,107] but also with overall survival and recurrence rate [100,107] . Furthermore, CT scans have shown that k19 was more frequently expressed in hypovascular HCCs, indicating a major risk of early recurrence [108] .…”
Section: Liver Biopsy (Percutaneous and Surgical Biopsy)mentioning
confidence: 99%
“…After further reading the fulltext, 8 articles were excluded due to duplication (n = 6), HR with 95% CI unavailable (n = 1) and scoring less than 6 (n = 1) [15]. Eventually, there were 17 studies included in this present meta-analysis [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] (Fig. 1).…”
Section: Literature Search Informationmentioning
confidence: 99%